Rapid diagnosis of pyrazinamide‐resistant multidrug‐resistant tuberculosis using a molecular‐based diagnostic algorithm. (16th July 2014) - Simons, S. O.; van der Laan, T.; Mulder, A.; van Ingen, J.; Rigouts, L.; Dekhuijzen, P. N. R.; Boeree, M. J.; van Soolingen, D.; Allerberger, F.
Abstract There is an urgent need for rapid and accurate diagnosis of pyrazinamide‐resistant multidrug‐resistant tuberculosis (MDR‐TB). No diagnostic algorithm has been validated in this population. We hypothesized that pncA sequencing added to rpoB mutation analysis can accurately identify patients with pyrazinamide‐resistant MDR‐TB. We identified from the Dutch national database (2007–11) patients with a positive Mycobacterium tuberculosis culture containing a mutation in the rpoB gene. In these cases, we prospectively sequenced the pncA gene. Results from the rpoB and pncA mutation analysis (pncA added to rpoB) were compared with phenotypic susceptibility testing results to rifampicin, isoniazid and pyrazinamide (reference standard) using the Mycobacterial Growth Indicator Tube 960 system. We included 83 clinical M. tuberculosis isolates containing rpoB mutations in the primary analysis. Rifampicin resistance was seen in 72 isolates (87%), isoniazid resistance in 73 isolates (88%) and MDR‐TB in 65 isolates (78%). Phenotypic reference testing identified pyrazinamide‐resistant MDR‐TB in 31 isolates (48%). Sensitivity of pncA sequencing added to rpoB mutation analysis for detecting pyrazinamide‐resistant MDR‐TB was 96.8%, the specificity was 94.2%, the positive predictive value was 90.9%, the negative predictive value was 98.0%, the positive likelihood was 16.8 and the negative likelihood was 0.03. In conclusion, pyrazinamide‐resistant MDR‐TB can be accurately detected using pncA sequencing added to rpoB mutation analysis. We propose to include pncA sequencing in every isolate with an rpoB mutation, allowing for stratification of MDR‐TB treatment according to pyrazinamide susceptibility.